Hubungan Kompensasi Dan Kepuasan Kerja Dengan Kinerja Pegawai Pada Dinas Lingkungan Hidup Kota Tangerang - Permana, Sandy Eka; Suhaya, Suhaya; Sabur, Ambuy; Mulyadi, Edi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
This study departs from the problem of employee performance, namely the low level of employee discipline. The purpose of the study was to analyze the relationship between compensation and job satisfaction with employee performance. The research method used is a quantitative method using a questionnaire as a tool for data collection. The samples taken were DLH Tangerang City employees as many as 121 employees from a population of 172 employees. Data analysis used correlation analysis and regression analysis. Based on the results of the analysis conducted, this study resulted in three conclusions: 1) There is a positive and significant relationship between compensation and employee performance, with a correlation coefficient of r = 0.216 > rtable (rtable = 0.195 at = 5%). 2) There is a positive and significant relationship between Job Satisfaction and Employee Performance, with a correlation coefficient r = 0.324 > rtable (rtable = 0.195 at = 5%). 3) There is a positive and significant relationship between Compensation and Job Satisfaction together with Employee Performance, with a correlation coefficient of R = 0.351 > Rtable (Rtable = 0.195 at α = 5%). Keywords: Compensation, Job Satisfaction, Employee Performance